Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Express $ z=-32 $ in exponential form.

My reasoning:

  1. $ z=-32 $ is the same as $ z=-32+0i $

  2. Exponential form should look like $ z=Re^{\theta i} $

  3. $ R =\sqrt{(-32)^2 + 0^2} = 32 $

  4. $ \theta = \tan^{-1}(\frac{0}{-32}) = 0 $

  5. So answer becomes: $ z = 32e^{0i} = 32 $

But, obviously, $ -32 \ne 32 $

What am I missing?

share|cite|improve this question
up vote 1 down vote accepted

Since $z=re^{i \theta}$, with $r\geq 0$, you must have $|z| = r$. So $r=32$. Then you need to solve $-32 = 32 e^{i \theta} = 32 (\cos\theta + i \sin \theta)$. Since the imaginary part is zero, you must have $\theta = n \pi$ for some integer $n$. Choosing $n$ to be odd gives all solutions, since $\cos n \pi = -1$ iff $n$ is odd.

Consequently $-32 = 32 e^{i n \pi}$, where $n$ is odd.

share|cite|improve this answer

$\tan^{-1}(0)$ could be both $0$ and $\pi$, and in your case, the second one fits.

$-32 = 32 e^{i\pi}$.

share|cite|improve this answer

The problem is with the inverse tangent that you're using to find the value of the argument of $-32$. Remember that the inverse tangent will give you values between $-\frac{\pi}{2}$ and $\frac{\pi}{2}$ so it is not giving you the correct argument.

In this case since $-32$ is in the negative real axis, its argument should be $\pi$ instead. Which will give you the "exponential form"

$$ -32 = 32e^{\pi i} $$

share|cite|improve this answer

As $R\cos\theta=-32<0=>\cos\theta<0$ and $\sin\theta=0$ so, $\theta$ lie in the 3rd quadrant $\pi ≤ \theta ≤ 3\frac{\pi}{2}$,

and $tan^{-1}(0)=n\pi$ where n is any integer.

So here, $\theta=(2m+1)\pi$ where m is any integer.

So, the general value of $-32=32e^{i(2m+1)\pi}$, the principal value being $32e^{i\pi}$

share|cite|improve this answer

$ -32 = -32(1 + 0 i) = -32 e^{i2n\pi}$

Or, $32(-1 + 0 i) = 32( \cos \pi + i \sin \pi) = 32 e^{i \pi}$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.